2010
DOI: 10.1128/aem.01369-10
|View full text |Cite
|
Sign up to set email alerts
|

Antiglycation Effects of Carnosine and Other Compounds on the Long-Term Survival of Escherichia coli

Abstract: Glycation, or nonenzymatic glycosylation, is a chemical reaction between reactive carbonyl-containing compounds and biomolecules containing free amino groups. Carbonyl-containing compounds include reducing sugars such as glucose or fructose, carbohydrate-derived compounds such as methylglyoxal and glyoxal, and nonsugars such as polyunsaturated fatty acids. The latter group includes molecules such as proteins, DNA, and amino lipids. Glycation-induced damage to these biomolecules has been shown to be a contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 42 publications
(45 reference statements)
2
58
0
1
Order By: Relevance
“…5). While the best-described roles of methylglyoxal as a metabolic poison do not correspond well with our metabolic measurements or with the reduced persister frequency observed in our ⌬glpD mutant, methylglyoxal has also been described as a protein-glycating agent (46), and it is interesting to speculate that the deleterious effects of glycation might be balanced either by reduced susceptibility to other protein damage or by the induction of protein maintenance and repair machinery. Possibly, a more complex effect of this nature could explain the transient but substantial increase in fitness that we observed for our ⌬pcm mutant in the presence of methylglyoxal.…”
Section: Discussionmentioning
confidence: 41%
“…5). While the best-described roles of methylglyoxal as a metabolic poison do not correspond well with our metabolic measurements or with the reduced persister frequency observed in our ⌬glpD mutant, methylglyoxal has also been described as a protein-glycating agent (46), and it is interesting to speculate that the deleterious effects of glycation might be balanced either by reduced susceptibility to other protein damage or by the induction of protein maintenance and repair machinery. Possibly, a more complex effect of this nature could explain the transient but substantial increase in fitness that we observed for our ⌬pcm mutant in the presence of methylglyoxal.…”
Section: Discussionmentioning
confidence: 41%
“…Further, the delay in glycation in TB and SB cultures is coincident with both delay of the death phase and delay in alkalization. This is expected since glycation levels have been shown to increase with medium pH (10,13,28). Our data show that higher glycation levels early during incubation correspond to a more severe death phase, and low glycation levels are coincident with a delay in the death phase.…”
Section: Discussionmentioning
confidence: 52%
“…It has previously been shown that advanced glycation end products (AGEs) accumulate during the LTSP (2, 10-13). In the presence of increasing concentrations of sugar (i.e., glucose), both the accumulation of AGEs and the severity of the death phase increase (10). To determine how glycation is affected by growth in different rich media, we quantified the amount of carboxymethyl lysine (CML), a common glycation end product, in cells cultured in LB, YT, TB, or SB, using an ELISA with an anti-CML antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations